Cassava thesaurus - Leatherdale, D. (International Center for Tropical Agriculture, 1977)
This structured vocabulary of terms related to cassava is divided into 2 sections: a categorized listing, giving the main relationships among the terms; and an alphabetical listing, giving the full array of relationships among the descriptors. The thesaurus was developed in order to assist the Cassava Information Center at CIAT in indexing and retrieving the large mass of cassava literature. (Abstracts on Tropical Agriculture)